P.048 Objective measures of balance deficits in sensory ganglionopathy. (June 2022) - Smith, CB; Beadon, K; Berger, M; Carpenter, M; Washbrook, C; Chapman, KM
Abstract : Background: Sensory ganglionopathy (SG) is a rare form of neuropathy affecting the dorsal root ganglia and leading to non-length-dependent sensory abnormalities. Although balance problems are frequently reported by patients, a comprehensive balance assessment in SG has not been conducted. This study quantifies balance deficits in SG and examines their relation to patient-reported outcome measures (PROMs). Methods: Prospective data was collected from five participants with SG. Balance assessments included Fullerton Advanced Balance scale, Berg Balance scale, and 360 degree turn. Participants completed PROMs assessing balance confidence (ABC scale), pain, fatigue, quality of life (QoL), and daily activity and participation. Assessment also included neurological exam, nerve conduction studies (NCS) and posturography. Results: All participants had severe SG on NCS with normal strength and significant sensory abnormalities. Balance scores indicated severe balance deficits in all participants and aligned with posturography and truncal sway measures. PROMs revealed low confidence in balance, high levels of pain and fatigue, difficulties with daily activities, and reduced QoL. Conclusions: Although balance testing is not part of routine clinical practice, PROMs and targeted assessment may help monitor patients with SG and their response to treatment. Larger sample sizes are needed to understand the impact of balance on PROMs and optimize bedside balance testing.